What Is the Reality of Hiatal Hernia Management?—A Registry Analysis - Köckerling, Ferdinand; Zarras, Konstantinos; Adolf, Daniela; Kraft, Barbara; Jacob, Dietmar; Weyhe, Dirk; Schug-Pass, Christine (Frontiers in Surgery, 2020)
Introduction To date, the guidelines for surgical repair of hiatal hernias do not contain any clear recommendations on the hiatoplasty technique with regard to the use of a mesh or to the type of fundoplication (Nissen vs. Toupet). This present 10-year analysis of data from the Herniamed Registry aims to investigate these questions. Methods Data on 17,328 elective hiatal hernia repairs were entered into the Herniamed Registry between 01.01.2010 and 31.12.2019. 96.4% of all repairs were completed by laparoscopic technique. One-year follow-up was available for 11,280 of 13,859 (81.4%) patients operated during the years 2010-2018. The explorative Fisher’s exact test was used for statistical calculation of significant differences with an alpha = 5%. Since the annual number of cases in the Herniamed Registry in the years 2010-2012 was still relatively low, to identify significant differences the years 2013 and 2019 were compared Results The use of mesh hiatoplasty for axial and recurrent hiatal hernias remained stable over the years from 2013 to 2019 at 20% and 45%, respectively. In the same period the use of mesh hiatoplasty for paraesophageal hiatal hernia slightly, but significantly, increased from 33.0% to 38.9%. The proportion of Nissen and Toupet fundoplications for axial hiatal hernia repair dropped from 90.2% in 2013 to 74.0% in 2019 in favor of “other techniques” at 20.9%. For the paraesophageal hiatal hernias (types II–IV) the proportion of Nissen and Toupet fundoplications was 68.1% in 2013 and 66.0% in 2019. The paraesophageal hiatal hernia repairs included a proportion of gastropexy procedures of 21.7% in 2013 and 18.7% in 2019. The recurrent hiatal hernia repairs also included a proportion of gastropexies 12.8% in 2013 and 15.1% in 2019, Nissen and Toupet fundoplications of 72.7% and 62.7%, respectively, and “other techniques” of 14.5% and 22.2%, respectively. No changes were seen in the postoperative complication and recurrence rates. Conclusion Clear trends are seen in hiatal hernia repair. The use of meshes has only slightly increased in paraesophageal hiatal hernia repairs. The use of alternative techniques has resulted in a reduction in the use of the “classic” Nissen and Toupet fundoplication surgical techniques